Bubston structure of water and electrolyte aqueous solutions. (September 2016) - Bunkin, N F; Bunkin, F V
Abstract: This paper develops the theoretical concept of a bubston, a stable gas bubble that exists in pure water and in electrolyte water solutions in equilibrium with their gaseous environment. A theoretical model of ion adsorption on a water surface is constructed and used to quantitatively describe the double electric layer that forms. These results also enable a thermodynamic description of a bubston structure in the water–gaseous environment system to be performed. It is shown that for certain temperatures and certain concentrations of dissolved impurity ions the emergence of such a structure is a first-order phase transition. The unique role of helium as a gaseous environment in the context under study is established: in this case, a bubston structure does not appear whatever the initial ion concentration, and the solubility of helium itself increases with increasing temperature. The mechanism of formation of experimentally observed bubston clusters is discussed.